Pengaruh Beban Kerja terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kabupaten Tanah Datar - Ledita Anastasya (Journal of Education on Social Science (JESS), 2019)
This study aims to determine whether the workload influential on the performance of nagari government apparatus in nagari financial management in Tanah Datar Regency. The background of this study was carried out because of the excessive workload received by the nagari government apparatus in nagari financial management in Tanah Datar Regency. This study uses a quantitative methods with population of this study was all nagari government apparatus, which numbered 600 people. Sample in this study was consisted of 248 nagari government apparatus determined with Slovin formula. Besides, sample in this study was determined through Multistage Random Sampling technique. The data was collected through questionnaires using Likert scale measurement. The data was analyzed with multiple linear regression tests. The results of this study showed that the workload variable (simultaneously) influenced the performance of nagari government apparatus in financial management in Tanah Datar Regency. This it could be concluded that workload had a significant effect on the performance of nagari government apparatus in nagari finance management in Tanah Datar Regency.